The Relationship Between Statistics Anxiety And The Efl Students’ Avoidance Of Quantitative Research: Case Of Postgraduate Students Of English, At The University Of Bejaia - Boughani, Siha (The Journal of Studies in Language, Culture, and Society, 2024)
Academic research focuses essentially on empirical processes when investigating educational phenomena as it provides credible and reliable results. On another side, statistics in social sciences and educational research have become the major issue of different research works. Regarding the importance of statistics, different disciplines emphasize the indispensability of integrating it into educational curricula. The majority of EFL students come from non-scientific disciplines and their attitudes towards scientific subjects-and particularly towards mathematics and statistics- are mostly negative. These negative attitudes create a kind of willingness to its avoidance because of uneasiness, stress and anxiety when studying statistics. Therefore in this study, the researcher tries to describe how stress towards statistics pushes students to avoid using quantitative methods and tools. To reach this aim, the procedures of an exploratory design were followed; in order to evaluate students’ attitudes towards research, a questionnaire is employed. Furthermore, a modified version of Papanastasiou’s Attitudes Toward Research (ATR) scale is used to measure the participants’ attitudes towards quantitative research on 5 point scale. Finally, Cruise’s et al. (1985) Statistics Anxiety Rating Scale (STARS) is utilized to define the factors leading to statistics anxiety and to check the correlation between quantitative research avoidance and statistics anxiety. The results show that there is a significant positive correlation between statistics’ anxiety and students’ reluctance towards the use of quantitative research procedures in their research studies.